The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/abd1806-4841.20131922
|View full text |Cite
|
Sign up to set email alerts
|

Proximal-type epithelioid sarcoma - Case report

Abstract: Epithelioid sarcoma, first described by Enzinger in 1970, is a rare soft-tissue sarcoma typically presenting as a subcutaneous or deep dermal mass in distal portions of the extremities of adolescents and young adults. In 1997, Guillou et al. described a different type of epithelioid sarcoma, called proximal-type epithelioid sarcoma, which is found mostly in the pelvic and perineal regions and genital tracts of young to middle-aged adults. It is characterized by a proliferation of epithelioid-like cells with rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…A staging CT scan revealed multiple metastases in the lungs and brain. The tumour exhibited an aggressive clinical course, with rapid distant metastasis and death nine months after diagnosis [ 16 ]. Stang et al reported a case of an 11-year-old girl who presented with a month-old swelling over the distal phalanx of the left middle finger.…”
Section: Discussionmentioning
confidence: 99%
“…A staging CT scan revealed multiple metastases in the lungs and brain. The tumour exhibited an aggressive clinical course, with rapid distant metastasis and death nine months after diagnosis [ 16 ]. Stang et al reported a case of an 11-year-old girl who presented with a month-old swelling over the distal phalanx of the left middle finger.…”
Section: Discussionmentioning
confidence: 99%
“…It was first described by Enzinger in 1970, typically presenting as a subcutaneous nodule or deep dermal mass in the distal extrimities. 2 Proximal variant was first described in 1997 by Guillou et al 5 Incidence is 0.04/million/yearin 2005 with male: female ratio being 1.8:1,with females having better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Although the literature reports an older age group in affected patients, our patient was just 17 years of age at presentation. [10] It typically shows large cells with prominent nucleoli, marked cytological atypia and intracytoplasmic hyaline inclusions. [11] These together impart a "RHABDOID" appearance to this variant.…”
Section: Discussionmentioning
confidence: 99%